Motivation factors on knowledge sharing in public sector organizations / Mohd Adib Suhaimi & Mohamad Anuar Sepe - Suhaimi, Mohd Adib; Sepe, Mohamad Anuar (2015)
Knowledge management plays an important role to increase public services delivery (Wigg, 1999). However, knowledge sharing may not happen if employees are not willing to share their knowledge and expertise. Davenport and Prusak (1998) states sharing knowledge is something difficult to an individual, and normally people may not share knowledge unless it is useful and beneficial to them (Ryu, Hee and Han, 2003).